Technology-Based Manipulatives - Bautista, Debbie Marie Y. (Archīum Ateneo, 2007)
One of the challenges confronting a Philippine mathematics teacher is the unavailability/lack of technology for use in the classroom. In this paper, we present technology-based manipulatives that provide opportunities for experimentation and discovery in the mathematics classroom as alternatives to the absence of technology. Models on Euclidean geometry, analytic geometry, trigonometry, and calculus will be discussed that can be used by students to observe and make conjectures on formulas and theorems.